Observation of Robust Néel Skyrmions in Metallic PtMnGa - Srivastava, Abhay K.; Devi, Parul; Sharma, Ankit K.; Ma, Tianping; Deniz, Hakan; Meyerheim, Holger L.; Felser, Claudia; Parkin, Stuart S. P. (Advanced Materials, 2020)
Over the past decade the family of chiral noncollinear spin textures has continued to expand with the observation in metallic compounds of Bloch-like skyrmions in several B20 compounds, and antiskyrmions in a tetragonal inverse Heusler. Néel like skyrmions in bulk crystals with broken inversion symmetry have recently been seen in two distinct nonmetallic compounds, GaV4S8 and VOSe2O5 at low temperatures (below ≈13 K) only. Here, the first observation of bulk Néel skyrmions in a metallic compound PtMnGa and, moreover, at high temperatures up to ≈220 K is reported. Lorentz transmission electron microscopy reveals the chiral Néel character of the skyrmions. A strong variation is reported of the size of the skyrmions on the thickness of the lamella in which they are confined, varying by a factor of 7 as the thickness is varied from ≈90 nm to ≈4 µm. Moreover, the skyrmions are highly robust to in-plane magnetic fields and can be stabilized in a zero magnetic field using suitable field-cooling protocols over a very broad temperature range to as low as 5 K. These properties, together with the possibility of manipulating skyrmions in metallic PtMnGa via current induced spin–orbit torques, make them extremely exciting for future spintronic applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Lorentz transmission electron microscopy; non-centrosymmetric; skyrmions; spintronics